Dialect Word Formation in Light of Linguistic Geography - Horvat, Mojca (Jezikoslovni zapiski, 2018)
This article presents word-formation studies of Slovenian dialects that use a geolinguistic method and technique; specifically, Slovenski lingvistični atlas (Slovenian Linguistic Atlas) and the Slavic Linguistic Atlas, as well as other independent dialect studies. The last part of the article presents a summary mapping of Slovenian dialect word-formation features based on thematically delimited material.